Variation in Botryosphaeriaceae from Eucalyptus plantations in YunNan Province in southwestern China across a climatic gradient - Guoqing Li; Bernard Slippers; Michael J. Wingfield; Shuaifei Chen (IMA Fungus)
ABSTRACT The Botryosphaeriaceae accommodates many important pathogens of woody plants, including Eucalyptus. Recently, Botryosphaeriaceae were isolated from diseased plant parts from surveys of Eucalyptus plantations in the YunNan Province, China. The aims of this study were to identify these Botryosphaeriaceae isolates and to evaluate their pathogenicity to Eucalyptus. A total of 166 isolates of Botryosphaeriaceae were obtained from six regions in the YunNan Province, of which 76 were from Eucalyptus urophylla × E. grandis hybrids, 49 from E. globulus trees, and 41 isolates were from other unknown Eucalyptus species or hybrids. Isolates were identified by comparing DNA sequences of the internal transcribed spacer ribosomal RNA locus (ITS), partial translation elongation factor 1-alpha (tef1), β-tubulin 2 (tub2) and DNA-directed RNA polymerase II subunit (rpb2) genes, and combined with their morphological characteristics. Eleven species were identified, including Botryosphaeria fusispora, B. wangensis, Lasiodiplodia pseudotheobromae, Neofusicoccum kwambonambiense, N. parvum, and six novel species described as B. puerensis, N. dianense, N. magniconidium, N. ningerense, N. parviconidium and N. yunnanense. The dominant species across the regions were N. yunnanense, N. parvum and B. wangensis, representing 31.3, 25.3 and 19.9% of the total isolates, respectively. Species diversity and composition changed across the different climatic zones, despite their relatively close geographic proximity and the fact that some of the species have a global distribution. All the Botryosphaeriaceae species were pathogenic to one-year-old plants of an E. urophylla × E. grandis clone and E. globulus seed-derived plants, but showed significant inter- and intra-species variation in aggressiveness amongst isolates. The study provides a foundation for monitoring and management of Botryosphaeriaceae through selection and breeding of Eucalyptus in the YunNan Province of southwestern China.